2012
DOI: 10.1021/jo202653b
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Enriched Compounds via a Tandem Enantioselective Reaction and Kinetic Resolution Polishing Sequence

Abstract: Herein we describe a tandem method of coupling an enantioselective reaction with a nonenzymatic kinetic resolution to prepare highly enantioenriched compounds. The procedure employs a moderately selective enantioselective reaction on a ketone or aldehyde to form an enriched alcohol followed by a kinetic resolution of the alcohol to generate ee's of >99% in yields greater than what is possible with a kinetic resolution. This method highlights an avenue to quickly acquire highly enriched compounds without develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, enantioselective reduction often requires significant optimization that will vary with ketone. Furthermore, an additional enantioselectivity polishing step is necessary for the moderately selective reductions to increase enantiomeric purity of chiral alcohol . Enzymatic reduction also provides access to enantiomerically enriched chiral alcohols, but it usually requires long lead optimization times and can only be performed on a limited number of ketone candidates during the typical discovery phase of a new drug …”
Section: Introductionmentioning
confidence: 99%
“…However, enantioselective reduction often requires significant optimization that will vary with ketone. Furthermore, an additional enantioselectivity polishing step is necessary for the moderately selective reductions to increase enantiomeric purity of chiral alcohol . Enzymatic reduction also provides access to enantiomerically enriched chiral alcohols, but it usually requires long lead optimization times and can only be performed on a limited number of ketone candidates during the typical discovery phase of a new drug …”
Section: Introductionmentioning
confidence: 99%
“…5 Kinetic resolutions with organic and organometallic catalyst have been studied in recent years. 6 Kagan et al found a variety of kinetic resolutions and opened up a modern study of kinetic resolution. 7 In recent articles, Aoyama et al…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic resolution can take many forms such as enzymatic or biocatalytic, 16 thermal (high or low temperature), 17 and organic or organometallic. 18,19 Kagan et al found a variety of kinetic resolution methods and laid the foundation for the modern study of kinetic resolution. 20 Kinetic resolution can be divided into roughly six categories, hydrolysis, reduction, oxidation, ring-opening, ringclosing, and other substituent changing reactions.…”
Section: Introductionmentioning
confidence: 99%